Strategies for five tumour markers in the screening and diagnosis of female breast cancer - Luo, Jun; Xiao, Jianbo; Yang, Yuwei; Chen, Gang; Hu, Dong; Zeng, Jiawei (Frontiers in Oncology, 2023)
Objective This study evaluated the diagnostic value of different combinations of five commonly used tumour markers and screened the best combination of tumour markers. Methods Regression analysis was used to evaluate 185 patients with suspected breast cancer admitted to Mianyang Central Hospital from January 2020 to December 2021. The differences of five tumour markers between a breast cancer group and a benign lesion group were analysed. The sensitivity and specificity of five tumour markers were compared. Results Of 185 patients with suspected breast cancer, 108 patients had breast cancer and 77 patients had benign breast tumours. The detection results of carcinoembryonic antigen (CEA), alpha fetoprotein (AFP), carbohydrate antigen 125 (CA125), carbohydrate antigen 199 (CA199) and carbohydrate antigen 153 (CA153) in patients with breast cancer were significantly higher than those in patients with benign breast tumours. In the analysis of the single-detection results of tumour markers, CEA had the highest sensitivity (23.94%), CA153 had the highest specificity (96.43%), AFP had the highest accuracy (47.66%) and CA153 had the highest area under the curve (AUC) value (0.727). With the increase of parallel indicators, the sensitivity, accuracy and AUC value increased in turn, and the increase was obvious in the front. The increase began to slow down after the three parallel indicators. Among the different combinations of three parallel detections of breast cancer tumour markers, the highest sensitivity was AFP + CEA + CA153 (83.46%), the highest accuracy was AFP + CEA + CA153 and AFP + CA153 + CA125 (80.25%), and the highest AUC was CEA + CA125 + CA199 (0.922). Conclusion AFP, CA153 and CA199 are recommended for clinical diagnosis of breast cancer. In routine physical examination and early breast cancer screening, the optimal combination of AFP + CEA + CA153 three parallel tests is recommended.